Efficient Estimation of the Costs of Rent Controls: A Comment - Moon, Choon-Geol; Stotsky, Janet G. (The Review of Economics and Statistics, 1993)
Steven B. Caudill, Richard W. Ault, and Richard P. Saba (1989) introduce an approach to estimating a hedonic price equation that accounts for censoring d ue to rent control in a rental housing market. This paper extends and clarifies their assertion on the consistency of the ordinary least squares estimates and their estimates. The authors indicate how the nature of the rent control law affects the consistency propertie s of the two estimation methods. Copyright 1993 by MIT Press.